Determination and analysis of monosaccharides in Polygonatum cyrtonema Hua polysaccharides from different areas by ultra‐high‐performance liquid chromatography quadrupole trap tandem mass spectrometry. Issue 18 (2nd September 2021) - Hu, Jiayi; Cheng, He; Xu, Jun; Liu, Junlin; Xing, Lihua; Shi, Suying; Wang, Rui; Wu, Zhendong; Yu, Nianjun; Peng, Daiyin
Abstract: We wanted to explore a new method for the determination of monosaccharides in Polygonatum cyrtonema Hua polysaccharide using the ultra‐high‐performance liquid chromatography quadrupole trap tandem mass spectrometry. In this study, hydrochloric acid was used instead of trifluoroacetic acid to hydrolyze polysaccharides, and hydrolysis time was greatly reduced from 5–9 h to 1 h. The 1‐phenyl‐3‐methyl‐5‐pyrazolone was used for pre‐column derivatization of monosaccharides. The parameters of linearity ( R 2  > 0.999), stability (1.63–2.52%), intra‐day and inter‐day precision (0.69–0.95%, 1.81–2.77%), repeatability (1.89–2.65%), and recovery (97.63–102.24%) of the method were verified. Satisfactory validation results showed this method could be used to determine the target components. The results indicated the polysaccharide contained glucose, mannose, rhamnose, galactose, ribose, and arabinose. Technique for order preference by similarity to an ideal solution and principal component analysis were used to build an evaluation model based on the monosaccharide composition. The evaluation results showed that the samples from the Qingyang County of Anhui Province were the best when the monosaccharides were used as the evaluation index. Therefore, a new method was established to detect the monosaccharide content of polysaccharides from Polygonatum cyrtonema Hua and comprehensively evaluate the quality of Chinese medicines with polysaccharides as the main active ingredient.